Expression of receptor advanced glycation end products (RAGE) and histological picture of pancreatic ï¢-cells of streptozotocin-induced diabetic rats after yellow soybean powder suspension (Glycine max) administration - Sri Kadarsih Soejono, Dominggos Gonsalves Sri Lestari Sulistyo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2012)
Diabetes mellitus is a multisystemic disease characterized by hyperglycemia due to defects ininsulin secretion and action, or both. Hyperglycemia is the most important factor in the onsetand progress of diabetic complications. Hyperglycemia increases the expression of receptor foradvanced glycosylation end products (RAGE) which leads to pancreatic ï¢-cells damage. Yellowsoybean (Glycine max) is reported to contain isoflavones which have various biological propertiesincluding antidiabetes. Dietary soybean can prevent the progression of diabetic complications.This study was conducted to investigate the effects of yellow soybean powder suspension onexpression of RAGE and pancreatic ï¢-cells damage of diabetic rats. Thirty streptozotocin (STZ)-induced diabetic Sprague Dawley male rats aged 11-12 weeks with body weight 200-250 g wereused in this study. The rats were divided into 5 groups with 6 rats in each group. Group 1 wasnon diabetic rats. Group 2 was diabetic rats without treatment. Group 3-5 were given yellowsoybean powder suspension of 400, 800 and 1600 mg/kg BW for four weeks, respectively. Atthe end of the experiment, pancreases tissues were removed for examination of RAGE expressionand pancreatic ï¢-cells. The results showed that yellow soybean powder suspension ingestionsignifantly decreased blood glucose level of diabetic rats toward normality (p<0.05). Moreover,the percentage of RAGE expression on Group 3 (50.01Â±2.75%) and Group 2 (53.03Â±4.02%)were not significantly different (p>0.05). Meanwhile, the percentage of RAGE expression onGroup 4 (42.43Â±4.08%) and Group 5 (40.62Â±3.42%) were significantly lower than Group 2(p<0.05). The percentage of pancreatic ï¢-cells on Group 2 (10.04Â±1.56%) was not significantlydifferent compared to Group 3 (8.61Â±0.81%) (p>0.05), whereas the percentage of pancreaticï¢-cells in Group 4 (16.78Â±7.79%) and in Group 5 (22.03Â±11.51%) were significantly higherthan Group 2 (p<0.05). In conclusion, yellow soybean powder suspension can decrease RAGEexpression and prevent pancreatic ï¢-cells damage on STZ-induced diabetic rats.Keywords: pancreatic ï¢cells - Langerhans islets - streptozotocine - diabetic rats - soybeans